Formulation and physicochemical and sensory characterization of an Andean Carchense flavored semi-mature cheese - Manríquez, María José (2021)
In this project, a semi-ripe flavored Andean from Carchi – Ecuador   type cheese was formulated and characterized in a physicochemical, sensory and microbiological way, using Pizán milk as raw material, genetically developed in the province of Carchi. An experiment was carried out in triplicate under a design completely randomized where two phases were developed, the first referring to the contextualization of the cheese evaluating raw material from two breeds of cattle, type of microorganisms and the final draining temperature, the best treatment was obtained through a sensory analysis, corresponding to a cheese made with milk from the Pizán race, lactic culture L. delbrueckii and L. helveticus, draining temperature of 44ºC and matured for 28 days, with this treatment the second phase was elaborated in which the addition of sauces and the coating to the crust, where the treatment made with milk from the Pizán race presented greater acceptability zán and lactic culture L. delbrueckii and L. helveticus, a dewatering temperature of 44ºC, flavored with pesto, matured for 28 days and with a coating of dehydrated species. Through sensory evaluation, the three best treatments were determined, these were subjected to an analysis of fat, protein and humidity, resulting in 39%, 10.5% and 51% respectively, percentages that are within the range established in the Ecuadorian Technical Regulations. NTE INEN 2607. In the microbiological analysis the absence of Enterobacteriaceae and Staphyloccocus aureus was determined, denoting that the product is completely harmless. Through these statements it can be concluded that the Pizán race milk meets the physicochemical parameters required for the production of ripened semi-hard cheeses, the milk of this breed is rich in macronutrients such as fat and proteins that provide unique texture, flavor and performance. typical of an Andean cheese.